Effect of Exercise Training on Physical Fitness Among Young Tennis Players: A Systematic Review - Xiao, Wensheng; Geok, Soh Kim; Bai, Xiaorong; Bu, Te; Norjali Wazir, Mohd Rozilee; Talib, Othman; Liu, Wenfang; Zhan, Chongjiang (Frontiers in Public Health, 2022)
Background: Physical fitness comprises both health and skill-related components that have been shown to correlate with athletes' competitive ability. Athletes' competitive ability is strongly related to the positive or poor characteristics of physical fitness. Additionally, the adolescent stage is critical for the development of physical fitness. Physical fitness training for young tennis players should receive more attention. However, the current literature is deficient in in-depth reviews of the effects of exercise training on the physical fitness of young tennis players. Objective: This review aims to investigate the effects of exercise training on physical fitness among young tennis players. Methods: From October 2020, a comprehensive search was undertaken in four electronic databases (SCOPUS, PubMed, EBSCOhost (SPORTDiscus), and CINAHL Plus), as well as on Google Scholar and other sources of grey literature references. The methodological quality of included studies was assessed using the Physiotherapy Evidence Database scale and the over scientific evidence was determined using the best evidence synthesis. This review included only studies that employed an experimental design to assess physical fitness components of young tennis players. Results: Nine articles on exercise training met all inclusion criteria and were included in this systematic review. The studies were of a high standard of quality. The research findings are relatively credible. The results indicated that speed (n=8) and agility (n=8) were the most often investigated performance characteristics in exercise training interventions with young tennis players, followed by power (n=7), strength (n=4), and flexibility (n=1). Exercise training significantly increased the physical fitness of young tennis players in terms of speed and agility. There is a lack of evidence about strength and flexibility. Meanwhile, there is conflicting evidence regarding the effect on power, and yet no evidence regarding the effect of exercise training on endurance. Conclusions: This systematic review established a compelling case for the beneficial effects of exercise training interventions on physical fitness in young tennis players. The review identifies current research gaps (i.e., athlete gender, with a particular emphasis on female athletes) that should be addressed in future experimental studies.